A genomic DNA segment from Petunia hybrida leads to increased transformation frequencies and simple integration patterns. - Meyer, P (1988)
A 2-kilobase (kb) genomic fragment was selected from Petunia hybrida that increased transformation efficiencies by at least a factor of 20 after direct DNA transfer to petunia and tobacco protoplasts when supercoiled plasmid DNA was used. Because of this effect this fragment was named transformation booster sequence (TBS). Increased transformation frequencies were observed for plasmids that contained either the 2-kb fragment in dimeric or monomeric form or an internal 1.1-kb fragment of TBS. Analysis of transformants revealed that preferentially one copy of foreign DNA is integrated. Thus, TBS improves the poor transformation frequencies of direct gene transfer using circular plasmids, while it conserves the simple integration pattern that is important for practical applications. Possible mechanisms of TBS action are discussed.